2013
DOI: 10.1097/aln.0b013e3182715d4d
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Fibrinogen Concentrate as First-line Therapy during Major Aortic Replacement Surgery

Abstract: Background: Fibrinogen is suggested to play an important role in managing major bleeding. However, clinical evidence regarding the effect of fibrinogen concentrate (derived from human plasma) on transfusion is limited. The authors assessed whether fibrinogen concentrate can reduce blood transfusion when given as intraoperative, targeted, first-line hemostatic therapy in bleeding patients undergoing aortic replacement surgery. Methods: In this single-center, prospective, placebocontrolled, double-blind study, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
196
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(209 citation statements)
references
References 38 publications
(66 reference statements)
9
196
1
3
Order By: Relevance
“…Fibrinogen concentrate was recently used as a first-line therapy in algorithm-based management of the bleeding patient. 12 In that first prospective, randomised study performed in patients undergoing aortic surgery, fibrinogen concentrate significantly reduced the transfusion of allogeneic blood products. 24 However, further well designed, prospective, randomised controlled trials assessing the efficacy and the safety of fibrinogen concentrate in cardiovascular surgery, in particular in the paediatric population, are required before such therapy could be recommended in routine practice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fibrinogen concentrate was recently used as a first-line therapy in algorithm-based management of the bleeding patient. 12 In that first prospective, randomised study performed in patients undergoing aortic surgery, fibrinogen concentrate significantly reduced the transfusion of allogeneic blood products. 24 However, further well designed, prospective, randomised controlled trials assessing the efficacy and the safety of fibrinogen concentrate in cardiovascular surgery, in particular in the paediatric population, are required before such therapy could be recommended in routine practice.…”
Section: Discussionmentioning
confidence: 98%
“…7,8 Fibrinogen concentrate has been used in Europe for many years in cases of congenital fibrinogen deficiency. 9 However, a growing literature in adults has demonstrated the efficacy of fibrinogen concentrate in patients with acquired hypofibrinogenaemia associated with trauma, 10 cardiac surgery 11,12 or massive bleeding. 13 This relatively new approach for fibrinogen replacement is based on (patho)physiological considerations.…”
Section: Introductionmentioning
confidence: 99%
“…While low fibrinogen levels have been associated with increased surgery-and traumarelated bleeding [5][6][7][8][9], persistently high fibrinogen levels are associated with an increased risk of acute coronary syndrome and ischemic stroke [10,11]. Targeting a fairly high FIBTEM maximum clot firmness (MCF) of 22 mm, first-line hemostatic therapy with fibrinogen reduced transfusion requirements after major thoracic and thoracoabdominal surgery as compared to placebo in an experimental clinical study setting [12]. Nevertheless, the target MCF levels for less invasive cardiac surgery and for trauma patients have not yet been clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…The role of fibrinogen supplementation for the treatment or prevention of bleeding in critical patients has been investigated [30 && ,31 && ]. For instance, in the frame of a placebo-controlled randomized trial including 61 patients undergoing aortic replacement surgery on cardiopulmonary bypass, the transfusion of allogeneic blood was dramatically reduced in patients receiving fibrinogen concentrate (median two versus 13 units, P < 0.001) [32]. Most importantly, a Cochrane review [33 & ] that was published in the past year on the use of fibrinogen supplementation in bleeding patients, including six randomized controlled trials with a total of 248 participants, found a beneficial effect of fibrinogen in reducing the incidence of allogeneic transfusions (RR 0.47, 95% CI 0.31-0.72).…”
Section: Fibrinogenmentioning
confidence: 98%